The Need to generate a Force Time History Towards Life Assessment of a Coil Spring / Y.S. Kong...[et al.] - Y.S., Kong; Abdullah, S.; Omar, M.Z; Haris, S.M; D., Schramm; T., Bruckmann (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This paper presents the generation of force time history for coil spring fatigue life predictions using cumulative trapezoidal numerical integration of acceleration time histories. Loading time history was a crucial element for fatigue life prediction but a suitable instrument for the data collection was not always available. Hence, the required force time histories were generated from two relative acceleration time histories. Acceleration time histories from vehicle sprung and un-sprung mass were collected and converted into displacement using cumulative trapezoidal numerical integration approach. Through regarding the spring as a linear component, the force time history was obtained. The force time history together with the spring finite element model were used as the input to fatigue life models for fatigue life prediction. The predicted fatigue lives for the coil spring were 3.12× 10-6, 5.67 × 10-6, 6.97 × 10-6 blocks to failure using Coffin-Manson, Morrow, Smith-Watson-Topper model respectively. The results were validated using measured strain time history where the Morrow and Smith-Watson-Topper models' results were fitted perfectly using the conservative correlation approach.